1997
DOI: 10.1161/01.cir.96.3.849
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity, Vascular Reactivity, and Clamp-Induced Vasodilatation in Essential Hypertension

Abstract: Metabolic insulin resistance in essential hypertension is not associated with abnormalities in vascular structure, acetylcholine or nitroprusside-induced vasodilatation, or vascular adrenergic reactivity. Degree of insulin sensitivity and acetylcholine sensitivity explain a small portion of the variability of the clamp-induced vasodilatation in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 32 publications
5
41
1
1
Order By: Relevance
“…To our knowledge, the present study is the first to report a direct association between insulin resistance and vascular endothelial dysfunction in type 2 diabetes, whereas such an association has not been observed in patients with obesity (14) or essential hypertension (15) or in normal subjects (13). This suggests a unique sensitivity of the endothelium of diabetic patients to the detrimental effect of insulin resistance; therefore, it is not surprising that treatment with tiazolidinediones has been shown to induce a concomitant amelioration of vascular endothelial function in type 2 diabetic (43) but not obese (14) patients.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…To our knowledge, the present study is the first to report a direct association between insulin resistance and vascular endothelial dysfunction in type 2 diabetes, whereas such an association has not been observed in patients with obesity (14) or essential hypertension (15) or in normal subjects (13). This suggests a unique sensitivity of the endothelium of diabetic patients to the detrimental effect of insulin resistance; therefore, it is not surprising that treatment with tiazolidinediones has been shown to induce a concomitant amelioration of vascular endothelial function in type 2 diabetic (43) but not obese (14) patients.…”
Section: Discussioncontrasting
confidence: 51%
“…In type 2 diabetes, however, no study has evaluated whether insulin resistance, when measured directly, clusters with these abnormalities. In normal (13) and obese (14) subjects and in patients with essential hypertension (15), the vascular response to endothelium-dependent vasodilators has been reported to be unrelated to insulin resistance. Previous studies in type 2 diabetes (Table 1) have generally found an impairment in endothelium-dependent vasodilatation; endothelium-independent dilatation, however, has been variably reported to be reduced or unaffected.…”
mentioning
confidence: 99%
“…Using the forearm technique, we have previously shown that EDV is reduced in diabetic patients in proportion to their degree of insulin resistance [46]. Insulin resistance, however, does not cluster with EDV in nondiabetic normotensive participants [47] or in patients with essential hypertension [48]. Therefore, we must postulate that long-standing hyperglycaemia on its own or in interaction with insulin resistance, directly or via accumulation of AGE compromises endothelium-dependent vascular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this is consistent with insulin's vasodilating properties in normal individuals and with graded amounts of insulin-induced vasodilation in hypertensives grouped by levels of insulin sensitivity. 24 However, levels of or changes in Ca cyt cannot be solely responsible for the state of smooth muscle contraction. As an example of this, the hypertensives with low Ca cyt clearly have a process ongoing that sustains their higher level of blood pressure, which may not be calcium mediated.…”
Section: Discussionmentioning
confidence: 99%